Answer:
Option b
Step-by-step explanation:
The question is shown in the attached image
To answer this question, we will simply substitute in the given expressions with the values y=2 and y=5
The correct option will be the one having equal vales in both cases
1. Option a:
At y = 2:
2y - 1 = 2(2) - 1 = 3
3y - 5 + y = 3(2) - 5 + 2 = 3
At y = 5:
2y - 1 = 2(5) - 1 = 10
3y - 5 + y = 3(5) - 5 + 5 = 15
This option is incorrect, since both expressions are not equal at y = 5
2. Option b:
At y = 2:
5y + 4 = 5(2) + 4 = 14
7y + 4 - 2y = 7(2) + 4 - 2(2) = 14
At y = 5:
5y + 4 = 5(5) + 4 = 29
7y + 4 - 2y = 7(5) + 4 - 2(5) = 29
This option is correct, since both expressions are equal at the two vales of y
3. Option c:
At y = 2:
y + 7 = 2 + 7 = 9
y + 2 + y = 2 + 2 + 2 = 6
At y = 5:
y + 7 = 5 + 7 = 12
y + 2 + y = 5 + 2 + 2 = 12
This option is incorrect, since both expressions are not equal at y = 2
4. Option d:
At y = 2:
3y - 4 = 3(2) - 4 = 2
3y - 2 + y = 3(2) - 2 + 2 = 6
At y = 5:
3y - 4 = 3(5) - 4 = 11
3y - 2 + y = 3(5) - 2 + 5 = 18
This option is incorrect, since both expressions are neither equal at y = 2 or y = 5
Hope this helps :)